2010
DOI: 10.1104/pp.109.149864
|View full text |Cite
|
Sign up to set email alerts
|

Strategic Distribution of Protective Proteins within Bran Layers of Wheat Protects the Nutrient-Rich Endosperm

Abstract: Bran from bread wheat (Triticum aestivum ‘Babbler’) grain is composed of many outer layers of dead maternal tissues that overlie living aleurone cells. The dead cell layers function as a barrier resistant to degradation, whereas the aleurone layer is involved in mobilizing organic substrates in the endosperm during germination. We microdissected three defined bran fractions, outer layers (epidermis and hypodermis), intermediate fraction (cross cells, tube cells, testa, and nucellar tissue), and inner layer (al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
62
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(67 citation statements)
references
References 44 publications
5
62
0
Order By: Relevance
“…NKD1 and NKD2 directly activate vp1 transcription and are predicted to directly 469 activate r1 ( Figure 7B; Supplemental Datasets 1, 2 and 3). endosperm and the only cell type alive at maturity; thus, it is fundamentally important for 478 defense to pathogens (Jerkovic et al, 2010). Among predicted direct targets was 479 xylanase inhibitor protein-1 (XIP-1), which is involved in fungal defense (Moscetti et al, 480 2013) Several key TFs were shown or predicted to be direct targets of NKD regulation, 492 including O2, PBF1, VP1 and R1.…”
Section: Functions Of Nkd1 and Nkd2 In Developing Endosperm 391mentioning
confidence: 99%
See 1 more Smart Citation
“…NKD1 and NKD2 directly activate vp1 transcription and are predicted to directly 469 activate r1 ( Figure 7B; Supplemental Datasets 1, 2 and 3). endosperm and the only cell type alive at maturity; thus, it is fundamentally important for 478 defense to pathogens (Jerkovic et al, 2010). Among predicted direct targets was 479 xylanase inhibitor protein-1 (XIP-1), which is involved in fungal defense (Moscetti et al, 480 2013) Several key TFs were shown or predicted to be direct targets of NKD regulation, 492 including O2, PBF1, VP1 and R1.…”
Section: Functions Of Nkd1 and Nkd2 In Developing Endosperm 391mentioning
confidence: 99%
“…BET cells transport nutrients from maternal tissue into the 44 developing endosperm. AL is important for digestion and remobilization of stored 45 reserves during germination as well as mineral storage and pathogen defense (Stewart 46 et al, 1988;Fath et al, 2000;Jerkovic et al, 2010). 47 4 To identify genes and biological processes directly or indirectly regulated by NKD1 and 91 NKD2 (NKD1/2) in developing endosperm, a transcriptomic analysis was undertaken to 92 identify gene transcripts differentially expressed (DE) between WT and nkd1 nkd2 93 mutant.…”
Section: Introduction 36mentioning
confidence: 99%
“…However, the outer layers (bran without aleurone), transfer cells, and the embryo (germ) remain less well characterized (Beaugrand, et al, 2005;Chen, et al, 2012;Jerkovic, et al, 2010;Robert, et al, 2011). Table 1.…”
Section: Cell Wallsmentioning
confidence: 99%
“…Outer layers / Bran without aleurone Arabinoxylan Wheat (Beaugrand et al, 2005;Beaugrand, Reis, et al, 2004;Philippe et al, 2006;Philippe et al, 2007); oat, rye, barley (13),(14)--D-glucan Wheat (Philippe et al, 2006) Callose Wheat (Philippe et al, 2006) Ferulic acid Wheat (Philippe et al, 2007) Xylanase Wheat (Beaugrand, Cronier, et al, 2004;Beaugrand et al, 2005;Beaugrand, Reis, et al, 2004) Oxalate oxidase Wheat (Jerkovic et al, 2010) Xylanase inhibitor I protein Wheat (Jerkovic et al, 2010) Wheatwin1 Wheat (Jerkovic et al, 2010) …”
Section: Part Of Grain Compound Crop and Referencesmentioning
confidence: 99%
See 1 more Smart Citation